The Speech Act of Request in Computer-Mediated Communication - Maria Miwita Rosari (Deskripsi Bahasa, 2020)
Through conversation ones establish relationship with others and keep channels open for further relationships. Politeness strategies and issues have been the focus of a number of studies. The way ones request for something to others depends on some factors such as the context they are in and the interlocutors they talk to. This article aims at developing the latest discussion on politeness phenomena by paying attention to the specifics of Computer-Mediated Communication (CMC) settings specifically an online discussion forum. This article attempts to identify how speech act of request is performed in Top Law School (TLS) online discussion forum. The data were analyzed to observe the forms of speech act of request and the types of speech act of request performed in the online discussion forum. The findings of this paper revealed that the forms of speech act of request are expressed by declarative, interrogative, and imperative sentence. Moreover, the types of speech act of request employed by the users are directive, indirective, and literal speech acts. The writer believes that the study will be beneficial and a good reference for future researchers in conducting research on pragmatics under the same topic. Hopefully, it will enrich readers’ knowledge and understanding of the speech act of request and the politeness in CMC.